Antibakteri Ekstrak Kulit Batang Manggis Hutan (Garcinia rigida miq.) - Elya, Berna; Soemiati, Atiek; Farida, Farida (UI Scholars Hub, 2009)
A research on the antibacterial activity of n-hexane extract and the ethyl acetate Garcinia rigida Miq. Bark against Salmonella typhosa ATCC 14028, Staphylo-coccus aureus ATCC 29213 dan Bacillus subtilis ATCC 6633 has been carried out. The research was included the determination of the growth inhibition zona with the cylinder diffusion method and the minimum inhibitory concentration with the petri dish dilution method. The result of this study showed that the n-hexane extract of Garcinia rigida Miq.bark did not give the growth inhibition zona to Salmonella typhosa ATCC 14028, Staphylococcus aureus ATCC 29213 and Bacillus subtilis ATCC 6633, but gave the minimum inhibitory concentration at 500 mg/ml for Sal-monella typhosa ATCC 14028, 250 mg/ml for Staphylococcus aureus ATCC 29213 and 125 mg/ml for Bacillus subtilis ATCC 6633. Whereas the ethyl acetate extract of Garcinia rigida Miq. bark gave the growth inhibition zona of concentra-tion 500, 250 and 125 mg/ml with average diameter to Salmonella typhosa ATCC 14028 were about 11.15, 9.05, 7.55 mm, to Staphylococcus aureus ATCC 29213 were about 14.25, 11.10, 8.95 mm and to Bacillus subtilis ATCC 6633 were about 20.97, 15.00, 10.07 mm. The minimum inhibitory concentration to ethyl acetate extract to Salmonella typhosa ATCC 14028, Staphylococcus aureus ATCC 29213 and Bacillus subtilis ATCC 6633 were about 250, 62,5 and 31,25 mg/ml respec-tively. As a conclusion, the ethyl acetate extract of Garcinia rigida Miq. bark had more better antibacterial activity than the n-hexane extract of Garcinia rigida Miq. Bark.